Insidad Bab al-Ijtihad dan Pengaruhnya Terhadap Madhhab Shafi’i - Luthfi Hadi Aminuddin (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2012)
This work is based on historcal Islamic legal development especially discourse of closing ijtihad ’authority’. Moslem and non-moslem specialist writers sure that this discourse happened pasca a’immat al-madhahib phase. This phase refers to the era when the creative thinking is stagnant. Amount of Shafi’ithe ulama> who state a binding ruling in religious matters of closing ijtihad authority, according to them, are responsible. This paper is to show that closing ijtiha>d ’authority’ discourse (insidad bab al-ijtihad) begins from the times when al-Ghaza>li>, al-Ra>fi’i>, and al-Nawa>wi> clasify mujtahid prerequsites. Their ’mujtahid qualifications’ are efforts which can close ijtiha>d ’authority’ (bab> al-ijtiha>d). Mujtahids did do Ijtiha>d as a creative thinking such as insha>’i> and intiqa>’i>. But they did this as mujtahid muntasib, mujtahid fi> al-madhhab or al-mujtahid al-murajjih as a different level from mujtahid mustaqill. Asha>b al-Sha>fi”˜i> such as al-Muzani>, al-Buwayti>, a-Juwayni>, al-Shayra>zi>, al-Ghaza>li>, al-Ra>fi”˜i> and al-Nawa>wi> standardize istinba>t method which Sha>fi’i> formulated.